Don't Lose Your Cool With Cryotherapy: The Application of Phase Change Material for Prolonged Cooling in Athletic Recovery and Beyond - Kwiecien, Susan Y.; McHugh, Malachy P.; Howatson, Glyn (Frontiers in Sports and Active Living, 2020)
Strenuous exercise can result in muscle damage in both recreational and elite athletes, and is accompanied by strength loss, and increases in soreness, oxidative stress, and inflammation. If the aforementioned signs and symptoms associated with exercise-induced muscle damage are excessive or unabated, the recovery process becomes prolonged and can result in performance decrements; consequently, there has been a great deal of research focussing on accelerating recovery following exercise. A popular recovery modality is cryotherapy which results in a reduction of tissue temperature by the withdrawal of heat from the body. Cryotherapy is advantageous because of its ability to reduce tissue temperature at the site of muscle damage. However, there are logistical limitations to traditional cryotherapy modalities, such as cold-water immersion or whole-body cryotherapy, because they are limited by the duration for which they can be administered in a single dose. Phase change material (PCM) at a temperature of 15°C can deliver a single dose of cooling for a prolonged duration in a practical, efficacious, and safe way; hence overcoming the limitations of traditional cryotherapy modalities. Recently, 15°C PCM has been locally administered following isolated eccentric exercise, a soccer match, and baseball pitching, for durations of three to six hours with no adverse effects. These data showed that using 15°C PCM to prolong the duration of cooling successfully reduced strength loss and soreness following exercise. Extending the positive effects associated with cryotherapy by prolonging the duration of cooling can enhance recovery following exercise and give athletes a competitive advantage.